ChemInform Abstract: Metal‐Organic Frameworks: From Molecules/Metal Ions to Crystals to Superstructures. Issue 28 (15th July 2014) - Carne‐Sanchez, Arnau; Imaz, Inhar; Stylianou, Kyriakos C.; Maspoch, Daniel
Abstract Review: [recently developed synthetic strategies to control the one‐, two‐ and three‐dimensional organisation of MOF crystals; 53 refs.